Congenital neutropenia with variable clinical presentation in novel mutation of the SRP54 gene. Issue 6 (11th April 2020) - Goldberg, Lior; Simon, Amos J.; Rechavi, Gideon; Lev, Atar; Barel, Ortal; Kunik, Vered; Toren, Amos; Schiby, Ginette; Tamary, Hannah; Steinberg‐Shemer, Orna; Somech, Raz
Abstract: Background: The SRP54 (signal recognition protein 54) is a conserved component of the ribonucleoprotein complex that mediates cotranslational targeting and translocation of proteins to the endoplasmic reticulum. In 2017, mutations in the gene have been described as a cause of congenital neutropenia with or without pancreatic insufficiency, and since then, only limited cases were added to the literature. Methods: Two patients with neutropenia underwent hematological, immunological, and genetic work‐up, including lymphocyte phenotyping, immunoglobulins, and complement levels, antineutrophil and antinuclear antibodies, bone marrow FISH panel for myelodysplastic syndrome, whole‐exome sequencing, and in silico proteomic analysis. Results: Clinical findings in the two families revealed a wide spectrum of immunological and clinical manifestations, ranging from mild asymptomatic neutropenia during febrile illnesses to severe neutropenia and life‐threatening infection requiring leg amputation. Immunological and hematological work‐up showed isolated neutropenia with normal lymphocyte subpopulations, immunoglobulin and complement levels, and negative autoimmune tests. Bone marrow aspirations showed variability ranging from normal myelopoiesis to myeloid maturation arrest at the promyelocytic stage, with normal FISH panel for myelodysplastic syndrome. Genetic analysis identified a novel, de novo, in‐frame deletion in the SRP54 gene, c.342‐344delAAC, p.T115del. In silico proteomic analysis suggested impaired SRP54 protein function due to reduced GTP activity and stability. Conclusions: We describe congenital neutropenia with variable clinical presentation in novel mutation of the SRP54 gene.